ANALISIS STRATEGI KOMUNIKASI MARKETING PT. QUIPPER DALAM INDUSTRI E-LEARNING SEBELUM DAN DI MASA PANDEMI COVID-19 - Ade Giovani; Zohrah Basalamah (Journal of Communication Sciences (JCoS), 2022)
This research aims to analyze the marketing communication strategy of PT. Quipper, a company in the e-learning industry, before and during the Covid-19 pandemic. The qualitative study found that the company initially implemented a Direct Marketing model and received positive market response, leading to expansion in 2016 by opening branch offices in 12 cities. PT. Quipper also developed a strategy using five models in the Marketing communication mix, including advertising, sales promotion, events and experiences, publicity, and personal marketing. However, the company faced competition from other companies providing material things to schools and had difficulty transitioning to online marketing during the pandemic.